Inventory of fine particulate organic compound emissions from residential wood combustion in Portugal - Gonçalves, Cátia; Alves, Célia; Pio, Casimiro (Atmospheric Environment, 2012)
In the early fall of 2010 a survey questionnaire was conducted to assess residential wood combustion (RWC) practices in the 18 districts of mainland Portugal. This paper describes and analyses the results from a bottom-up approach, based on this telephone survey, which enabled the characterisation of RWC practices in each district. Additionally, emission factors and source proﬁles obtained from different RWC tests, allowed the estimation of CO, CO2, PM2.5 and particulate organic compound emissions on a country-scale. The type and number of RWC appliances, each with their speciﬁc emissions factor and the amount and type of fuel used vary signiﬁcantly on a district scale. The energy consumption in RWC appliances was estimated to be 35 342 TJ y 1 . The estimated emissions of PM2.5 from RWC in Portugal (10.96 kt y 1 ) represent 30% of the estimate for different source activities reported in a recent inventory. The national emissions of OC and EC were estimated to be 5.32 and 0.53 kt y 1 , respectively. It was also estimated that the total CO2 emissions from RWC in Portugal are 1.7 Mt y 1 . The levoglucosan emissions contribute with between 7.8% and 16.1% of PM2.5 emissions from RWC
The following values have no corresponding Zotero field: publisher: Elsevier Ltd
Keywords: Burning appliances; Emission factors; Inventory; survey questionnaire; Wood species

Emission factors from residential combustion appliances burning Portuguese biomass fuels - Fernandes, A. P.; Alves, C. A.; Goncalves, C.; Tarelho, L.; Pio, C.; Schimdl, C.; Bauer, H. (Journal of Environmental Monitoring, 2011)
Smoke from residential wood burning has been identified as a major contributor to air pollution, motivating detailed emission measurements under controlled conditions. A series of experiments were performed to compare the emission levels from two types of wood-stoves to those of fireplaces. Eight types of biomass were burned in the laboratory: wood from seven species of trees grown in the Portuguese forest (Pinus pinaster, Eucalyptus globulus, Quercus suber, Acacia longifolia, Quercus faginea, Olea europaea and Quercus ilex rotundifolia) and briquettes produced from forest biomass waste. Average emission factors were in the ranges 27.5-99.2 g CO kg-1, 552-1660 g CO2 kg-1, 0.66-1.34 g NO kg-1, and 0.82-4.94 g hydrocarbons kg-1 of biomass burned (dry basis). Average particle emission factors varied between 1.12 and 20.06 g kg-1 biomass burned (dry basis), with higher burn rates producing significantly less particle mass per kg wood burned than the low burn rates. Particle mass emission factors from wood-stoves were lower than those from the fireplace. The average emission factors for organic and elemental carbon were in the intervals 0.24-10.1 and 0.18-0.68 g kg-1 biomass burned (dry basis), respectively. The elemental carbon content of particles emitted from the energy-efficient "chimney type" logwood stove was substantially higher than in the conventional cast iron stove and fireplace, whereas the opposite was observed for the organic carbon fraction. Pinus pinaster, the only softwood species among all, was the biofuel with the lowest emissions of particles, CO, NO and hydrocarbons.
The following values have no corresponding Zotero field: publisher: The Royal Society of Chemistry
Keywords: Biomass combustion; Emission factors; Wood stove (voyant)

VOC Emissions from Cork Products for Indoor Use - Horn, W.; Ullrich, D.; Seifert, B. (Indoor Air, 1998)
Abstract Complaints about unpleasant odour from wall, ceiling and floor coverings made of composite cork, induced chamber tests to study the emissions of volatile organic compounds (VOC) from composite cork products for indoor use. Emissions of phenol and furfural were found to be high, particularly those from cork parquet. Emission factors after 1 week ranged from 150 to 650 μg m−2 h−1 and from 15 to 350 μg m−2 h−1 for phenol and furfural, respectively, and decreased only slowly over time, by a factor of approx. 10 for a 6-month period. The ranges of emission factors were found to be similar for some solvents such as cyclohexanone or toluene which are constituents of varnishes used to protect cork surfaces. The emission of furfural may result from chemical reactions in the cork during the production process or may be caused by additives such as binders.
The following values have no corresponding Zotero field: publisher: Munksgaard International Publishers
Keywords: Chamber measurements; Composite cork; Emission factors; Furfural; Phenol

Isoprenoid emission of oak species typical for the Mediterranean area: Source strength and controlling variables - Steinbrecher, Rainer; Hauff, Karin; Rabong, Richard; Steinbrecher, Jutta (Atmospheric Environment, 1997)
easurements of isoprenoid emission on five Mediterranean oak species in the field revealed that Quercu.s frainetto, Quercus petraea and Quercus pubescens are strong emitters of isoprene. In contrast Quercus cerris and Quercus suber emitted no significant amounts of isoprene and monoterpenes. For Q. pubenscens and Q. frainetto median emission factors of 16.68 nmoIm-2s-1 (86.06 pgg-’ dw h-‘) and 30.72 nmolrn-2s-1 (133.95 pgg-’ dw h-l) were calculated, respectively. The 25 to 75 percentiles span of the emission factor data sets ranged from - 53% to + 56% of the median values. Light and temperature are the main controlling factors for isoprene emission. The influence of other environmental and plant physiological parameters on the isoprene emission is discussed. The “Guenther” emission algorithm is able to predict the daily maximum of the isoprene emission within the plant specific uncertainty range. However, the morning increase and the afternoon drop in the isoprene emission is not well parameterized. On the basis of process oriented models for the synthesis of isoprene in plants, a further reduction in the uncertainty may be achieved resulting in a more reliable prediction of short-time variation in isoprene emission
Keywords: biogenic voc; Emission factors; isoprene; Monoterpene; Quercus

Isoprenoid emission of oak species typical for the Mediterranean area: Source strength and controlling variables - Steinbrecher, Rainer; Hauff, Karin; Rabong, Richard; Steinbrecher, Jutta (Atmospheric Environment, 1997)
easurements of isoprenoid emission on five Mediterranean oak species in the field revealed that Quercu.s frainetto, Quercus petraea and Quercus pubescens are strong emitters of isoprene. In contrast Quercus cerris and Quercus suber emitted no significant amounts of isoprene and monoterpenes. For Q. pubenscens and Q. frainetto median emission factors of 16.68 nmoIm-2s-1 (86.06 pgg-’ dw h-‘) and 30.72 nmolrn-2s-1 (133.95 pgg-’ dw h-l) were calculated, respectively. The 25 to 75 percentiles span of the emission factor data sets ranged from - 53% to + 56% of the median values. Light and temperature are the main controlling factors for isoprene emission. The influence of other environmental and plant physiological parameters on the isoprene emission is discussed. The “Guenther” emission algorithm is able to predict the daily maximum of the isoprene emission within the plant specific uncertainty range. However, the morning increase and the afternoon drop in the isoprene emission is not well parameterized. On the basis of process oriented models for the synthesis of isoprene in plants, a further reduction in the uncertainty may be achieved resulting in a more reliable prediction of short-time variation in isoprene emission
Keywords: biogenic voc; Emission factors; isoprene; Monoterpene; Quercus